Case Report: Catatonia Associated With Post-traumatic Stress Disorder - Ahmed, Gellan K.; Elbeh, Khaled; Karim, Ahmed A.; Khedr, Eman M. (Frontiers in Psychiatry, 2021)
We report here about a 12-year-old female patient who had two life-threatening accidents that led to post-traumatic stress disorder associated with catatonia. She had closed eyes, had urinary and fecal incontinence, and had been in an abnormal position for one and half month. Moreover, she had complications such as dehydration, malunion of the fractured arm, and deformities in hand and foot. After detailed psychiatric examination, neurological assessment, and laboratory investigation, the patient received successful treatment in the form of benzodiazepine injections, intravenous fluid, oral antidepressants, and six sessions of electroconvulsive therapy (ECT). We discuss the pathophysiology of catatonia, which remains elusive, and recommend evaluating catatonic children for any possible trauma during psychiatry assessment.